273Cell to cell communication: miRNA involvement. (15th July 2014) - Climent Salarich, M; Condorelli, G; Elia, L
Abstract: Background: Cardiometabolic diseases (CMD) are the primary cause of death and disability in the Western world. The recent developments in genetics and genomics provide a background for further investigating this area with the aim of deepening our understanding of the atherosclerotic phenomena underlying CMD. MicroRNAs (miRs) are short, non-coding RNAs that negatively regulate gene expression, and are involved in cardiovascular diseases. The cross talk between the different cell types of the vessel wall is fundamental in order to maintain the vessel integrity. This phenomenon is dysregulated during atherosclerosis development, inducing a modulation of smooth muscle cells (SMCs) and endothelial cells (ECs) biology. Methods/Results: The aim of this study is to understand whether the SMC-specific miR-143 and -145 might be transferred to ECs, then modulating their biological activity. Indeed, our data revealed that vascular stress is associated with down-regulation of miR-143 and -145 in SMCs: their modulation is responsible for SMC phenotypic switch from a contractile/non proliferative to a migratory/proliferative state. We observed that ECs, which do not normally express miR-143 and -145, do so after being co-cultured with SMCs, indicating that these miRs can be transferred from SMCs to ECs. ECs fed with SMC-conditioned media did not express miR-143 and -145. Instead, direct contact between the two cells types triggered the transfer of the miRs. This indicated that the transfer is not guided by any paracrine mechanism. Then, we observed that the transfer is restricted only to the mature miR sequences as no primary-miR-143/145 could be detected in ECs after co-culture. Conclusion: Our data suggest that dysregulation of miR-143 and -145 genes is causally involved in aberrant SMC plasticity and probably in endothelial pathophysiology encountered during vascular disease.